Prints and Plates : 23 Quebec Printmakers : The Lavalin Collection. (Montreal : Lavalin Inc., 1982)
Belley, Irené ; Bercovitch, Myrna ; Boisvert, Gilles ; Bougie, Louis-Pierre ; Bruneau, Kittie ; Charbonneau, Monique ; Cloutier, Paul ; Daoust, Carl ; Derouin, René ; Gheerbrant, Gilles ; Landori, Eva ; Lau, Tin-Yum ; Leroux-Guillaume, Janine ; Lindsay, Doreen ; Lui, Andrew ; etc.
Prints and Plates : 23 Quebec Printmakers : The Lavalin Collection, Man ad His World, June 23 to August 29, 1982 / Calgary, September 9 to October 2, 1982 / etc.
boek